Stunting Prevention Through Nutritional Education for Mothers and Children in Nagari Kajai, Pasaman Barat Regency - Aprihatin, Yessy; Anggia Sari, Dwi Happy; Prarikeslan, Widya; ErpitaYanti, ErpitaYanti (Sumatra Journal of Disaster, Geography and Geography Education, 2022)
Stunting is a condition of chronic malnutrition during growth and development since early life. West Pasaman Regency is one of the provinces in West Sumatra which tends to experience an increase in stunting prevalence from 2007 to 2017, although there was a decline in 2018, the prevalence is still high at 35.2 (Riskesdas, 2018). To overcome this problem, it is important to conduct health education through the use of a healthy diet to prevent growth retardation. The purpose of this non-profit service is to increase knowledge and understanding of mothers in stunting prevention through health education to mothers and children, so that direct motivation from mothers is expected to be able to optimally pay attention to their growth and development. from children. The method used is to examine maternal knowledge and the problems of stunting prevention and early detection of stunting in Nagari Kajai. Mother's knowledge was measured by pre-test health education and post-test health education. Based on the pre and post test results from 21 respondents, 10 respondents (47.61%) understood about stunting prevention and it increased after health education was carried out where 17 respondents (80.95%) understood about stunting prevention, data were collected before health counseling was carried out. It is hoped that Nagari Kajai mothers will always follow a healthy diet for their children and receive ongoing support from cadres to prevent stunting and reduce stunting in West Pasaman Regency, especially Nagari Kajai.